(untitled) (Research, Society and Development, 2022)
This study aims to describe safety practices in a hospital after the implementation of the Patient Safety Center Commission. Descriptive, retrospective, quantitative and documentary study, based on data from the collection of this committee, referring to the years 2020 and 2021, and eight hospitalization sectors of the hospital were evaluated. The results showed that, in relation to the identification of the patient, there was no safe protocol or use of white bracelets to identify the patients, while the location of beds with full name presented 100% support in 2021. For the prevention of risk of falls, the hospital did not have a protocol, but there was an improvement in the treatment of medications that cause drowsiness at night and in the maintenance of a safe environment. In the prevention of pressure injury, there was no established safety protocol; on the other hand, improvement in risk assessment practices of this type of injury on admission, and availability of pneumatic mattresses. Regarding safety in the drug process, the research pointed out the lack of an established protocol, but there was a reduction in carbonated prescriptions, with 100% support in 2021; use of printed for refrigerator temperature control record; and control of medications used in cardiorespiratory arrest by validity and quantity. The data indicated advances in the patient safety process after the implementation of this committee, but pointed out the need to implement the organizational culture of patient safety for the evolution of the goals.